Knowledge and self-care practice among patients with hypertension in tertiary public hospitals of Addis Ababa, Ethiopia: A multicenter cross-sectional study - Freweini Gebremeskel Gebresilase; Yohannes Ayalew Bekele; Ketema Bizuwork Gebremedhin; Boka Dugassa Tolera (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Globally, hypertension is the leading cause of death due to its related complications. Patients’ knowledge and self-care practice in hypertension is crucial for achieving optimal blood pressure control and prevention of related complications. This study aimed to evaluate the level of knowledge and self-care practice among hypertensive patients in Addis Ababa, Ethiopia. Methods: A facility-based cross-sectional study was conducted among 413 hypertensive patients using simple random sampling methods. A face-to-face interview was administered using a structured questionnaire. Data was analyzed using SPSS version 27.0. Frequency percentage, and mean were calculated. Multivariable logistic regression was used to identify the association between predictors and outcome variables. Results: Out of 413 respondents, 46.0 % (95 % CI: 40–50 %) and 40.9 % (95 % CI: 36–46 %) had poor knowledge and self-care practice respectively. Being married (AOR = 1.92, 95 % CI:1.19–3.06, P = 0.007), higher education [AOR = 7.38 (95 % CI: 2.29–23.78), P < 0.001); family history (AOR = 3.68, 95 % CI: 2.28–5.94, P < 0.001); getting information from healthcare providers (AOR = 3.17, 95 % CI: 1.46–6.87, P = 0.003) were significantly associated with knowledge of hypertension. Being female (AOR: 0.62,95 % CI: 0.39–0.97, P = 0.033), owing sphygmomanometer (AOR: 4.41,95 % CI: 2.40–8.13, P < 0.001) were associated with self-care practice towards hypertension. Conclusion: The overall knowledge and self-care practice of respondents was low. Gender, marital status, educational level, family history, source of information, and owing sphygmomanometer were determinant factors. Improving patients’ awareness and self-care practice is essential for prevention and control of hypertension.